2022
DOI: 10.3390/biomimetics7020065
|View full text |Cite
|
Sign up to set email alerts
|

Effective Microorganism Solution and High Volume of Fly Ash Blended Sustainable Bio-Concrete

Abstract: Currently, the production of sustainable concrete with high strength, durability, and fewer environmental problems has become a priority of concrete industries worldwide. Based on this fact, the effective microorganism (EM) solution was included in the concrete mixtures to modify the engineering properties. Concrete specimens prepared with 50% fly ash (FA) as an ordinary Portland cement (OPC) replacement were considered as the control sample. The influence of EM solution inclusion (at various contents of 0, 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Carbonic anhydrases and Ureases like enzymes catalyze this bio-sequestration process, which is produced by microorganisms (Alshalif, et al, 2022). Through another study, it was revealed that the usage particular concentration of fly ash content with selected microorganism solutions can significantly improve the compressive strength of concrete while preventing the formation of microcracks (Huseien et al, 2022).…”
Section: Concrete Mixturementioning
confidence: 99%
“…Carbonic anhydrases and Ureases like enzymes catalyze this bio-sequestration process, which is produced by microorganisms (Alshalif, et al, 2022). Through another study, it was revealed that the usage particular concentration of fly ash content with selected microorganism solutions can significantly improve the compressive strength of concrete while preventing the formation of microcracks (Huseien et al, 2022).…”
Section: Concrete Mixturementioning
confidence: 99%
“…One of these methods involves the integration of microbial broth directly into the fresh concrete as a partial replacement for water [ 44 , 45 ]. EMs have shown immense benefits when incorporated into concrete [ 44 ], wherein the strength properties of the fresh mixes (particularly at the early ages) and cement hydration reaction processes were improved, thus enhancing the microstructures [ 44 , 46 ]. In addition, EMs have significant influence on the viscosity of the prepared mixing water (Ems–Water) [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EMs have significant influence on the viscosity of the prepared mixing water (Ems–Water) [ 45 ]. Hussein et al [ 42 ] reported an increase in the viscosity of Ems–Water from 0.95 to 1.25 mPa (as the mixing water replacement) when the EMs content was increased from 0 to 25% [ 44 ]. Wang et al [ 47 ] claimed that added water viscosity has strong potential to influence both fresh and hardened properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations